The Painful Hip in Young Adults Between Impingement and Mild Dysplasia: Clinical and Instrumental Diagnostical Criteria - Lorenzon, Paolo; Scalvi, Andrea; Scalco, Enrico (Acta Biomedica Atenei Parmensis, 2020)
Femoroacetabular impingement and developmental dysplasia of the hip are among the main causes of hip arthritis. In absence of degenerative alterations of the hip, there is the chance of a surgical conservative treatment. This study aims to show the clinical and imaging criteria to a correct and prompt diagnosis.